Covid-19 infection in liver transplanted patients - Hyppolito, Elodie Bomfim (2021)
SARS-Cov-2 (Covid-19) infection is a new clinical condition that has had a profound impact on the entire health system in the world, causing a significant reduction in the performance of organ transplants. The natural history of Covid-19 in liver transplant recipients is unknown. Purpose: To assess clinical manifestations, liver involvement, access to the healthcare system, and mortality of SARS-COV-2 infection (COVID-19) in liver transplanted patients at HUWC-UFC. Methods: We retrospectively assessed in a cross-sectional, observational study a series of 58 suspected cases of COVID-19 in liver transplanted patients at HUWC- UFC. Of these, 18 cases were confirmed to be SARS-CoV-2-infected. Results: The epidemiological profile of this series was that 13 individuals were male, with average age of 58.8 years (Δ35 to 75 years), mean liver transplantation time of 5 years (Δ0.5 to 11 years). All patients in this case series had some comorbidity, with diabetes, overweight and SAH being the most frequent. Most of these patients were treated in a hospital setting, but not all had access to chest tomography, RT-PCR for SARS-CoV-2 or intensive care when necessary. Of the 18 patients, 5 patients died due to coronavirus complications, the majority due to respiratory failure, resulting in a lethality rate of 27.8%. Conclusion: We conclude that Covid-19 infection had high lethality in liver transplanted patients at HUWC-UFC.